Technologies and Teacher's Motivational Style: A Research Study in Brazilian Public Schools - Magda Pischetola; Bruna Damiana Heinsfeld (LED Edizioni Universitarie, 2018)
Information and Communications Technology (ICT) is increasingly a part of discussions on educational innovation and teaching practices. Research from the last decade points out the difficulty of integrating technologies in education and highlights the variety of elements favouring/preventing change in teaching and learning methods. In this article, we defend that the methodology adopted by teachers, their approach with regard to students in the classroom and what literature calls educational professionals' «motivational style» (Decy & Ryan, 1985 and 2000; Reeve, Bolt, & Cai, 1999; Guimarães & Boruchovitch, 2004; Pischetola, 2016) are the elements that most lead to a significant role for ICT in teaching practices. The discussion relies on self-determination theory and the assumption of the existence of more autonomy-supportive or more controlling teacher's motivating styles. Based on this premise, we present here a qualitative study undertaken between 2014 and 2016 at eight municipal primary schools in the city of Rio de Janeiro, Brazil. As a whole, we undertook 64 semi-structured interviews with teachers from the selected schools. The obtained results have allowed us to demonstrate a relationship between teachers' motivational style with the use of technology and the creation (or otherwise) of a dialogue-based and democratic space in the classroom.